Impact of Foreign Investment on Indonesia: Analysis of Socio-Legal Problems - Ivanovenska Ardya Aqilla Yudhistira (Fakultas Hukum Dehasen, 2023)
Foreign Direct Investment (FDI) has become a pivotal element in Indonesia's development over the past few decades. The presence of foreign capital in Indonesia has made a significant contribution to economic growth, yet it has also been accompanied by a range of issues and challenges that need to be addressed. This article aims to conduct an in-depth analysis of the impact of FDI on Indonesia's economic growth and elaborate on the issues that arise within the context of socio-legal. This study combines qualitative and quantitative approaches to analyze the impact of FDI across various socio-legal context, mainly economics, sociological, and legal aspects. The research findings indicate that FDI has played a pivotal role in accelerating Indonesia's economic growth, generating employment opportunities, and transferring technology. However, these positive impacts are counterbalanced by issues such as income inequality, shifts in social dynamics, and legal and regulatory concerns. The article also outlines several prospects that can guide future policy development. These include enhancing cooperation between the government and foreign investors, improving workers' rights protection, and increasing transparency and efficiency in FDI licensing. Environmental sustainability and social inclusion also constitute critical focal points in addressing the challenges at hand. Hence, this journal provides a comprehensive insight into the impact of FDI on Indonesia's economic growth while highlighting the issues that demand further attention. This study serves as a roadmap for policy makers, stakeholders, and researchers to formulate a more effective strategies in maximizing the benefits of FDI while addressing the challenges that arise.